The Maze of Taste: On Bataille, Derrida, and Kant - Arkady Plotnitsky (Studies in 20th & 21st Century Literature, 1988)
The case of Kant's Critique of Judgment offers a powerful example of the radical disruption of the metaphysical text, enacted by Bataille's major сoncepts. The analysis of the metaphor of economy in Kant, Bataille and Derrida suggests the crucial importance of Bataille's general economy—as the economy of loss—for deconstructing the Kantian conception of genius and the whole scheme of taste—as an economy of consumption—and inscribing a complex interplay forces that the general economy is designed to account for. Once however taste, art and the economy of genius can no longer be inscribed through the restricted economy of the metaphysical text, the question of genre and style of a different inscription—a general economy—acquires a crucial significance. Bataille's own discursive practice can be seen as an exemplification of such a different—plural— style.
Keywords: Kant; Critique of Judgment; metaphysical; metaphysical text; Bataille; metaphor; Derrida; economy; economy of loss; genius; scheme of taste; economy of consumption; art; plurality; German philosophy; modern philosophy